Post-placental postpartum intrauterine contraceptive devices insertion: our scenario - Soni, Monica; Sharma, Vatsala; Bhat, Madhu Patni; Sharma, Anita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: India is the second most populous country in the world with a population estimate of 1,304,162,999 on 1st January 2016. Population explosion is a great menace for the country and effective population control is the need of the hour. This study was designed to evaluate postpartum intrauterine contraceptive devices (PPIUCD), which is a novel innovation in population control. Methods: This was a prospective study with a sample size of 300 women (150 cesarean and 150 vaginal deliveries). After informed consent and assessing eligibility for PPIUCD, Cu-T 380A was inserted. Post-insertion, the cases were followed up to 12 weeks after delivery with special attention to acceptance and complications like IUCD expulsion, hemorrhage, pelvic pain and infection. The results were compiled and statistically analyzed. Results: Acceptance of PPIUCD was higher in Cesarean deliveries than in vaginal deliveries. Acceptance was also higher in unplanned pregnancies. Presence of prior male child influenced decisions. Minor complications were reported but there were no serious complications. No expulsions were reported in post-cesarean cases. Conclusions: PPIUCD, a long-acting reversible method of contraception, is a safe option with high retention rate and very few expulsions and side effects. There was higher rate of acceptance, no expulsion and high continuation rate in post-cesarean cases as compared to vaginally delivered cases.